Outcomes of Furlow Double-Opposing Z-Plasty Palatoplasty for the Treatment of Symptomatic Overt and Occult Submucous Cleft Palate: A Comparison Study. Issue 5 (27th April 2021) - Brooker, Jack E.; Bykowski, Michael; Cray, James J.; Beiriger, Justin; Roy, Eva; Ford, Matthew D.; Grunwaldt, Lorelei; Davit, Alexander; Goldstein, Jesse A.; Jabbour, Noel; Losee, Joseph E.
Abstract : Background: The submucous cleft palate can be overt or occult and may require surgical repair. The double-opposing Z-plasty (Furlow repair) is the authors' center's preferred approach. This study evaluated complication rates, differences in outcome between overt and occult types, and patient factors associated with surgical failure. Methods: This retrospective study reviewed documentation on all patients who underwent Furlow Z-plasty for submucous cleft palate at a single center between 2004 and 2018. Speech pathology was quantified using the Pittsburgh Weighted Speech Score. Results: A total of 351 patients were included (125 overt and 226 occult cases). Furlow Z-plasty was successful (postoperative Pittsburgh Weighted Speech Score <7 without recommendation for secondary speech surgery) in 291 patients (82.1 percent). Apart from those requiring secondary surgery, there were no documented complications. Occult-type patients were 7.5 years old at palatoplasty with a speech score of 14.1; overt-type patients were 6.5 years old with a score of 15.7. Postoperative speech scores were similar for both groups. Secondary speech surgery patients had a higher preoperative score (16.9 versus 14.2). Age at time of palatoplasty and submucous cleft palate type were not predictive of the need for secondary surgery. Syndromic patients had higher preoperative and postoperative speech scores (15.6 and 7.5, respectively) than nonsyndromic patients (14.3 and 4.3) and needed secondary surgery more often (24.4 percent versus 9.2 percent). V-shaped velar vaulting on preoperative assessment was present in 92 percent of occult-type patients. Conclusions: Furlow palatoplasty is a safe and effective means of repairing submucous cleft palate. Patients with the occult type presented later with a lower Pittsburgh Weighted Speech Score. High preoperative speech score and syndromic status were associated with the need for secondary speech surgery. V-shaped velar vaulting is a reliable sign of occult submucous cleft palate. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.